Rescue of Noradrenergic System as a Novel Pharmacological Strategy in the Treatment of Chronic Pain: Focus on Microglia Activation - Caraci, Filippo; Merlo, Sara; Drago, Filippo; Caruso, Giuseppe; Parenti, Carmela; Sortino, Maria Angela (Frontiers in Pharmacology, 2019)
Different types of pain can evolve towards a chronic condition characterized by hyperalgesia and allodynia, with an abnormal response to normal or even innocuous stimuli, respectively. A key role in endogenous analgesia is recognized to descending noradrenergic pathways that originate from the locus coeruleus and project to the dorsal horn of the spinal cord. Impairment of this system is associated with pain chronicization. More recently, activation of glial cells, in particular microglia, towards a pro-inflammatory state has also been implicated in the transition from acute to chronic pain. Both α2- and β2-adrenergic receptors are expressed in microglia and their activation leads to acquisition of an anti-inflammatory phenotype. This review analyses in more detail the interconnection between descending noradrenergic system and neuroinflammation, focusing on drugs that, by rescuing the noradrenergic control, exert also an anti-inflammatory effect, ultimately leading to analgesic effect. More specifically the potential efficacy in the treatment of neuropathic pain of classes of drugs will be analyzed. On one side drugs acting as inhibitors of the reuptake of serotonin and noradrenaline, such as duloxetine and venlafaxine, on the other, tapentadol, inhibitor of the reuptake of noradrenalin and agonist of the µ-opioid receptor.